Blunted cerebral blood flow velocity in response to a nitric oxide donor in postural tachycardia syndrome - Del Pozzi, Andrew T. (American Physiological Society, 2014)
Cognitive deficits are characteristic of postural tachycardia syndrome (POTS). Intact nitrergic nitric oxide (NO) is important to cerebral blood flow (CBF) regulation, neurovascular coupling, and cognitive efficacy. POTS patients often experience defective NO-mediated vasodilation caused by oxidative stress. We have previously shown dilation of the middle cerebral artery in response to a bolus administration of the NO donor sodium nitroprusside (SNP) in healthy volunteers. In the present study, we hypothesized a blunted middle cerebral artery response to SNP in POTS. We used combined transcranial Doppler-ultrasound to measure CBF velocity and near-infrared spectroscopy to measure cerebral hemoglobin oxygenation while subjects were in the supine position. The responses of 17 POTS patients were compared with 12 healthy control subjects (age: 14–28 yr). CBF velocity in POTS patients and control subjects were not different at baseline (75 ± 3 vs. 71 ± 2 cm/s, P = 0.31) and decreased to a lesser degree with SNP in POTS patients (to 71 ± 3 vs. 62 ± 2 cm/s, P = 0.02). Changes in total and oxygenated hemoglobin (8.83 ± 0.45 and 8.13 ± 0.48 μmol/kg tissue) were markedly reduced in POTS patients compared with control subjects (14.2 ± 1.4 and 13.6 ± 1.6 μmol/kg tissue), primarily due to increased venous efflux. The data indicate reduced cerebral oxygenation, blunting of cerebral arterial vasodilation, and heightened cerebral venodilation. We conclude, based on the present study outcomes, that decreased bioavailability of NO is apparent in the vascular beds, resulting in a downregulation of NO receptor sites, ultimately leading to blunted responses to exogenous NO.